2014
DOI: 10.1097/acm.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and the Career Satisfaction of Male and Female Academic Medical Faculty

Abstract: Purpose To explore aspects of mentoring that might influence medical faculty career satisfaction and to discover whether there are gender differences. Method In 2010–2011, the authors surveyed 1,708 clinician–researchers who received (in 2006–2009) National Institutes of Health K08 and K23 awards, which provided mentoring for career development. The authors compared, by gender, the development and nature of mentoring relationships, mentor characteristics, extent of mentoring in various mentor roles, and sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 30 publications
2
138
2
2
Order By: Relevance
“…According to three systematic reviews regarding mentoring in academic medicine (Sambunjak et al 2006(Sambunjak et al , 2010Kashiwagi et al 2013), the effects of mentorship vary among studies. It shows that having a mentor exerts an effect on specialty choice, career choice in research, career satisfaction, gender equality, leadership promotion, and career development (Feldman et al 2010;DeCastro et al 2014). Corroborating the results of our study, several previous studies have reported mentors' positive effect on publishing research (Levinson et al 1991;Palepu et al 1998;Curtis et al 2003;Steiner et al 2004), completing a thesis (Sciscione et al 1998;Ramondetta et al 2003) and obtaining a grant (Palepu et al 1998;Curtis et al 2003;Steiner et al 2004).…”
Section: Discussionsupporting
confidence: 66%
“…According to three systematic reviews regarding mentoring in academic medicine (Sambunjak et al 2006(Sambunjak et al , 2010Kashiwagi et al 2013), the effects of mentorship vary among studies. It shows that having a mentor exerts an effect on specialty choice, career choice in research, career satisfaction, gender equality, leadership promotion, and career development (Feldman et al 2010;DeCastro et al 2014). Corroborating the results of our study, several previous studies have reported mentors' positive effect on publishing research (Levinson et al 1991;Palepu et al 1998;Curtis et al 2003;Steiner et al 2004), completing a thesis (Sciscione et al 1998;Ramondetta et al 2003) and obtaining a grant (Palepu et al 1998;Curtis et al 2003;Steiner et al 2004).…”
Section: Discussionsupporting
confidence: 66%
“…It is notable, however, that all league members have remained in academia for more than a decade and have successfully advanced on the academic ladder, despite evidence that women in academia often have difficulty finding suitable mentors. 17 …”
Section: Discussionmentioning
confidence: 99%
“…a Of note, presence/availability of female mentors had no association with mentee satisfaction in some studies (4,5) and had a positive association in some studies (28,32,36). b Female mentors were perceived as less accessible and more controlling.…”
Section: Take Personal Responsibility Change the Landscapementioning
confidence: 99%
“…Mentorship in general has been explored, as well as gender specific differences or issues that arise. The literature is comprised largely of surveys (1)(2)(3)(4)(5)(6)(7)(8), commentaries (9-12), reviews (13)(14)(15)(16), and interviews (17). Very few studies show causality, or active intervention and outcomes of mentorship programs (8,18,19).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation